Model Pembelajaran Berdiferensiasi dalam Kurikulum Merdeka - Ahmad Zain Sarnoto (Journal on Education, 2024)
This research aims to find out how differentiated learning models are in the independent curriculum. In differentiated learning, teachers must pay attention to the individual needs of each student, identify different abilities, interests and learning styles, and choose appropriate teaching strategies for each student. In addition, teachers also need to provide various choices in learning activities and assessments, so that students can choose how to learn and assess themselves. The findings of this research show that the implementation of the differentiated learning model in the independent learning curriculum pays attention to the principles of individuality, comprehensive learning achievement, motivation, context or student background, student interests and needs, normalization, assessment and integration.